solve the following equation
Attachments:
![](https://hi-static.z-dn.net/files/d20/74726a298d87205aeab481022cea99b6.jpg)
Answers
Answered by
1
Answer:
x=3
Step-by-step explanation:
if it is helpful for you then mark me as a brainliest
Attachments:
![](https://hi-static.z-dn.net/files/df1/3edf3a82e9d161fc9925f683665d9ea8.jpg)
Answered by
0
Answer:
x = 3
Step-by-step explanation:
(4x+3)-9x = 6
(7-5x)-2x 7
4x+3-9x = 6
7-5x-2x 7
3-5x = 6
7-7x 7
7(3-5x) = 6(7-7x)
21-35x = 42-42x
-35x+42x = 42-21
7x = 21
x = 21/7
x = 3
Similar questions